The mobility of nitrogen across tree‐rings of Norway spruce (Picea abies L.) and the effect of extraction method on tree‐ring δ15N and δ13C values. (20th April 2014) - Tomlinson, G.; Siegwolf, R. T. W.; Buchmann, N.; Schleppi, P.; Waldner, P.; Weber, P.
<x xml:space="preserve">Abstract</x> RATIONALE The use of stable nitrogen (N) isotope ratios (δ15N values) in dendroecological studies is often preceded by an extraction procedure using organic solvents to remove mobile N compounds from tree‐rings. Although these mobile N compounds may be capable of distorting potential environmental signals in the tree‐ring δ15N values, recent investigations question the necessity of such an extraction. METHODS We used an on‐going experiment with simulated elevated N deposition previously labelled with 15N, in conjunction with control trees, to investigate the necessity of extracting mobile N compounds (using a rapid extraction procedure) for tree‐ring δ15N and δ13C studies, as well as N and C concentration analyses. In addition, we examined the magnitude of radial redistribution of N across tree‐rings of Norway spruce (Picea abies). RESULTS The 15N label, applied in 1995/96, was found in tree‐rings as far back as 1951, although the increased N availability did not cause any significant relative increase in tree growth. The rapid extraction procedure had no significant effect on tree‐ring δ15N or δ13C values in either labelled or control trees, or on N concentration. The C concentrations, however, were significantly higher after extraction in control samples, with the opposite effect observed in labelled samples. CONCLUSIONS Our results indicate that the extraction of mobile N compounds through the rapid extraction procedure is not necessary prior to the determination of Norway spruce δ15N or δ13C values in dendrochemical studies. δ15N values, however, must be interpreted with great care, particularly when used as a proxy for the N status of trees, due to the very high mobility of N within the tree stem sapwood of Norway spruce over several decades. Copyright © 2014 John Wiley & Sons, Ltd.